Methylation patterns of estrogen receptor α promoter correlate with estrogen receptor α expression and clinicopathological factors in hepatocellular carcinoma. (July 2014) - Dai, Binghua; Geng, Li; Yu, Yong; Sui, Chengjun; Xie, Feng; Shen, Weifeng; Zheng, Tao; Yang, Jiamei
Hepatocellular carcinoma (HCC) is the seventh most common type of cancer; notably, the incidence of HCC is four to eight times higher in men than women. Previous studies reported that the estrogen receptor (ER) signaling pathway is involved in the pathogenesis of HCC, although the extent of its involvement is unclear due to several conflicting reports. In the present study, tumor and paired adjacent non-cancerous tissues from 157 HCC patients were collected. Transcriptome sequencing and real-time quantitative polymerase chain reaction were used to quantify the ER α (ESR1) expression levels, and the Sequenom EpiTYPER assay was used to delineate the methylation patterns in the ESR1 promoter. We found that ESR1 expression was significantly reduced in tumor tissues ( P  < 0.001) compared to adjacent non-cancerous tissues. The CpG sites around the transcription start site were significantly hypermethylated in the tumor ( P  < 0.0001). This methylation pattern also correlated with the gene expression ( P  < 0.0001). Additionally, we found that the hypermethylation of ESR1 was associated with the presence of fibrous capsules ( P  = 1.2 × 10 −4 ), the absence of microvascular invasions ( P  = 8.0 × 10 −4 ), thin trabecular pattern ( P  = 0.025), and lower histologic gradings ( P  = 5.2 × 10 −3 ). Thus, ESR1 expression is a candidate tumor suppressor gene in HCC. Further, promoter hypermethylation may be a mechanism by which expression of ESR1 is repressed, and the extent of hypermethylation of ESR1 may be a marker for HCC status and progression.